Nigerian income tax law and practice - Ola, C. S. (London : Macmillan Publishers, 1985)
The author in writing this book intended it to make the subject interesting and to provide a regular supply of a suitable text to law and accountancy students.
Includes bibliographical references and index.
rpm 25/01/2019
Loans
Keywords: Income tax; Nigeria